Skin Findings in Williams Syndrome - Kozel, Beth A. (2014)
Previous examination in a small number of individuals with Williams syndrome (also referred to as Williams-Beuren syndrome) has shown subtly softer skin and reduced deposition of elastin, an elastic matrix protein important in tissue recoil. No quantitative information about skin elasticity in individuals with Williams syndrome is available; nor has there been a complete report of dermatologic findings in this population. To fill this knowledge gap, 94 patients with Williams syndrome aged 7-50 years were recruited as part of the Skin and Vascular Elasticity (WS-SAVE) study. They underwent either a clinical dermatologic assessment by trained dermatologists (2010 WSA family meeting) or measurement of biomechanical properties of the skin with the DermaLab™ suction cup (2012 WSA family meeting). Clinical assessment confirmed that soft skin is common in this population (83%), as is premature graying of the hair (80% of those 20 years or older), while wrinkles (92%) and abnormal scarring (33%) were detected in larger than expected proportions. Biomechanical studies detected statistically significant differences in dP (the pressure required to lift the skin), dT (the time required to raise the skin through a prescribed gradient), VE (viscoelasticity) and E (Young’s modulus) relative to matched controls. The RT (retraction time) also trended longer but was not significant. The biomechanical differences noted in these patients did not correlate with the presence of vascular defects also attributable to elastin insufficiency (vascular stiffness, hypertension, and arterial stenosis) suggesting the presence of tissue specific modifiers that modulate the impact of elastin insufficiency in each tissue.